HOTEL COMPLEX DEVELOPMENT: PRINCIPLE CONCEPT - Konovalova, Elena (Revista Inclusiones, 2020)
The contemporary Russian market of hotel services was formed under the influence of historical aspects of the hotel enterprises functioning according to the old Soviet type of the planned economy, as well as using Western models of successful development of hotel chains. This hybrid scenario implied the use of traditional world approaches to the formation of hotel concepts as basic participants in the tourist market. However, in modern reality, it is necessary to revise this approach due to its low efficiency at the stage of the strategic development of business units. The strategic development of hotel enterprises, their ability to conceptualize and implement new forms of providing qualitatively new models of hotel services are the key to the successful functioning of the tourism market, and therefore the industry development. The problems of forming and developing successful concepts for multifunctional hotel complexes remain understudied. The solution to these problems in the context of developing an effective methodology for analyzing the organizational development processes and the ability of enterprises to the sustainable progression of tourism activities in traditional tourist destinations remains quite relevant issue in tourist industry.